AKTIVITAS ENZIM SUPEROKSIDA DISMUTASE TIKUS DIABETES YANG DIBERI EKSTRAK DAUN KAPULAGA Amomum cardamomum - Putri Eka Sari; Sorta Basar Ida Simanjuntak; Hery Winarsi (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Diabetes is a disease characterized by abnormal insulin secretion, production, and insulin resistance. This condition cause oxidative stress which produce radical anion superoxide and decrease superoxide dismutase (SOD) activity. SOD is an antioxidant enzyme that can reduces anion superoxide which caused by diabetes. Many natural medicine are believed having the capacity to improve antioxidant status in the body. Cardamom’s leaf was reported containing flavonoids and vitamin C has been proven as in vitro antioxidant. However, there is no data that shows in vivo potency. This study was aimed to know the SOD activity of diabetic rats after treatment of cardamom’s leaf extract. This research used experimental method consist 2 treatment and 5 repetitions. First treatment was diabetic rats given a dose of 100mg/kg body mass of cardamom’s leaf extract (CLE) and second treatment was diabetic rats without CLE as control every day for 21 days. Blood sampling was performed 4 times : 0, 7, 14, 21 after treatment. Parameter measured were inhibition of ferricytokrom C reduction. Data were analyzed using unpaired t test. The result showed the highest SOD activity was 506.60 U/mg protein (P<0.01) in diabetic rats for 14 days CLE. The conclusions of this research are SOD activity increased after 14 days treatment of cardamom’s leaf extract.